Hamburger Sternwarte plate archives: Historic long‐term variability study of active galaxies based on digitized photographic plates. Issue 1 (15th February 2017) - Wertz, M.; Horns, D.; Groote, D.; Tuvikene, T.; Czesla, S.; Schmitt, J. H. M. M.
Abstract : Background: At the Hamburger Sternwarte, an effort was started in 2010 with the aim of digitizing its more than 45, 000 photographic plates and films stored in its plate archives. At the time of writing, more than 31, 000 plates have already been made available on the Internet for researchers, historians, and the interested public. Materials and Methods: The digitization process and the Internet presentation of the plates and accompanying handwritten material (plate envelopes, logbooks, observer notes) are presented here. To fully exploit the unique photometric and astrometric data, stored on the plates, further processing steps are required including registering the plate to celestial coordinates, masking of the plates, and a calibration of the photoemulsion darkening curve. To demonstrate the correct functioning of these procedures, historical light curves of two bright BL Lac‐type active galactic nuclei are extracted. Results: The resulting light curve of the blazar 1ES 1215+303 exhibits a large decrease in the magnitude from 14 . 2 5 − 0 . 12 + 0 . 07 to 15 . 9 4 − 0 . 13 + 0 . 09 in about 300 days, which proves the variability in the optical region. Furthermore, we compare the measured magnitudes for the quasar 3C 273 with contemporaneous measurements and find good agreement.